Codon usage tabulated from the international DNA sequence databases. - Nakamura, Y (1997)
The codon usage in individual protein genes has been calculated using the nucleotide sequence obtained from the GenBank Genetic Sequence Database. Sum of the codon use of each organism has been also calculated. The data files can be obtained from anonymous ftp sites of DDBJ, DISC and EBI. The list of codon usage of genes in organisms was made searchable by name of organism through a web site. The compilation has been synchronized with a major release of GenBank.